Lack of in vivo and in vitro bactericidal activity of N-formimidoyl thienamycin against enterococci. - Auckenthaler, R (1982)
The minimal bactericidal concentrations of N-formimidoyl thienamycin (N-f-thienamycin) against 21 strains of enterococci isolated from patients with infective endocarditis were determined by macro- and microdilution methods. By a macrodilution technique with the minimal bactericidal concentration defined as greater than or equal to 99.9% killing of an initial inoculum, all 21 strains of enterococci were found to have minimal bactericidal concentration/minimal inhibitory concentration ratios of greater than or equal to 32. The mean minimal inhibitory concentration was 1.5 micrograms/ml (range, 0.5 to 4 micrograms/ml), and the minimal bactericidal concentration was greater than or equal to 128 micrograms/ml. The disparity between the results of our study and those published elsewhere, which reported that N-f-thienamycin is bactericidal in vitro against enterococci, may represent the relative insensitivity of the microdilution method in determining greater than or equal to 99.9% killing. The lack of in vitro bactericidal activity of N-f-thienamycin against enterococci was confirmed in vivo in the rabbit model of experimental endocarditis. N-f-Thienamycin was no more effective than penicillin alone in the treatment of experimental enterococcal endocarditis and was less effective than the combination of penicillin and gentamicin. The results indicate that N-f-thienamycin should not be used alone in the treatment of enterococcal endocarditis.